Does social media pay for music artists? Quantitative evidence on the co-evolution of social media, streaming and live music - Allan Watson; Joseph B Watson; Louise Tompkins-Tinari (2022)
Recent commentaries on the music industry have emphasised the importance of social media in creating a monetisable fan base. However, no quantitative evidence yet exists regarding the correlation between social media follower numbers and artist income. Using a unique dataset of 255 artists signed to a large UK-based independent music publisher, we undertake growth curve modelling to provide a novel quantitative analysis of the correlation between following across major social media and streaming platforms and royalty income from music rights. Findings from our modelling suggest that while there is no correlation between numbers of followers on major social media platforms and an artist’s total royalty earnings, there is a strong correlation between numbers of followers and royalties from music streaming specifically. Set in the context of the high level of income precarity being experienced amongst independent artists, this finding suggests that a positive co-evolution is occurring between social media platforms and music streaming with potentially significant increases in artist royalty incomes resulting from increases in followers. Similarly, our modelling identifies a strong correlation between an artist’s following on streaming platforms and total live music royalties, supporting the notion of a positive co-evolution between streaming and live music incomes.